Pengaruh Customer Experience, Halal Awareness, Dan Customer Engagement Terhadap Customer Loyalty Melalui Customer Satisfaction: Studi Pada Konsumen Online Madu PT Kembang Joyo Sriwijaya - Fawwaz Achmad Najib; Abdullah Syakur Novianto; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of Customer Experience, Halal Awareness, and Customer Engagement on Customer Loyalty mediated by Customer Satisfaction among online consumers of PT Kembang Joyo Sriwijaya honey products. This research uses a quantitative approach with a purposive sampling technique involving 130 respondents who have purchased the product online. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results indicate that Customer Experience and Customer Engagement have a positive and significant effect on Customer Satisfaction and Customer Loyalty. However, Halal Awareness proved to have no significant effect on either satisfaction or loyalty, indicating that halal certification is considered a hygiene factor rather than a satisfier in this industry. Furthermore, Customer Satisfaction successfully mediates the relationship between Customer Engagement and Customer Loyalty, but fails to mediate the influence of Customer Experience and Halal Awareness. These findings suggest that to increase loyalty, the company should focus on building active engagement and ensuring a seamless customer experience, rather than solely relying on halal labeling. Keywords: Customer Experience, Halal Awareness, Customer Engagement, Customer Satisfaction, Customer Loyalty, PT Kembang Joyo Sriwijaya, SmartPLS, Honey.